KISAH KISKINDHĀ KĀNDA RAMĀYĀNA SEBAGAI REFLEKSI PEMBELAJARAN GUNA MEMPERERAT IKATAN PERSAUDARAAN - Darma Permana, I Dewa Gede (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The story of Kiskindhā Kānda is one part of the Ramayāna book which contains a sublime story and various conflicts in it. Among these various conflicts, there is one part that becomes the core of the story when two wanara brothers, namely Vālī and Sugrīva, are involved in a feud. The conflict reflects a less harmonious relationship between brothers, and seems similar to some cases that occur in life today. Reflecting on this, this study is interested in examining more deeply the story of the Kiskindhā Kānda Ramāyāna to find a deeper reflection of its learning, especially in the perspective of Hindu religious teachings. To support this goal, this research formulates several problems, namely related to the content of the story of Kiskindhā Kānda Ramāyāna, the nature of moral teachings in Hinduism, and finally formulating learning reflections that can be used as guidelines in living life. By using qualitative research methods, and literature studies, and using data analysis from Miles and Huberman. The results of this study indicate that the story of Kiskindhā Kānda Ramāyāna contains various learning reflections aimed at maintaining brotherly bonds so that they remain stable, harmonious, loyal, and helping each other.